Determination of decolorization properties of Reactive Blue 19 dye using Horseradish Peroxidase enzyme - Celebi, Mithat; Altikatoglu, Melda; Akdeste, Zeynep Mustafaeva; Yildirim, Huseyin (WALTER DE GRUYTER GMBH, 2013)
Aim: Fenolic compounds are major of pollutants in medicine, food and local matrixe. The enzyme peroxidase is known for its capacity to remove phenolic compounds and aromatic amines from aqueous solutions and also to decolorize textile effluents. In this study, decolorization of anthraquinone dye, Reactive Blue 19 (RB 19), large quantities of which used in textile and other industries was investigated using Horseradish peroxidase (HRP) at different conditions. In addition, decolorization efficiency of dye by enzyme was studied in the presence of denaturing agent urea and salt in synthetic wastewater. Material and Methods: Horseradish peroxidase and Reactive Blue 19 were obtained by commercial way. The enzymatic decolorization of the dye was examined by UV-Vis spectrophotometer measurements. Decolorization studies were performed by varying parameters such as enzyme and dye concentrations, pH, temperature, incubation time, presence of H2O2, salt and urea. Results: Optimum pH value for dye decolorization was determined as 5.0. Maximum dye was removed within 5 min after the beginning for every experiment. After 5 minutes of treatment, the color removal of dye was ca. 90-95% at pH 5.0 and all temperatures. Furthermore, the higher concentrations of dye, H2O2 and NaCl did not exhibit inhibition effect but the initial decolorization rate decreased with increasing the urea concentration. The kinetic constants of enzyme were determined for dye. Conclusion: As a result, this study verifies the viability of the use of the horseradish peroxidase in the decolorization of Reactive Blue 19.
Keywords: Dye decolorization; Reactive Blue 19 (RB 19); Horseradish peroxidase (HRP); textile dye; industrial effluents; WHITE-ROT FUNGI; PHANEROCHAETE-CHRYSOSPORIUM; PLEUROTUS-OSTREATUS; CULTURE FILTRATE; AQUEOUS-SOLUTION; SYNTHETIC DYES; TEXTILE DYES; WASTE-WATER; AZO DYES; DEGRADATION; Biochemistry & Molecular Biology